Islamic education in Singapore: a continuing debate - Sahib Babu , Hikmatullah (IIUM Press, International Islamic University Malaysia, 2004)
Islamic education and its continued relevance to modern Singapore has been an engaging topic for some time. The challenges taking shape in the wider Islamic world has direct influence on madrasah education. This paper is a modest attempt to situate the reality of Islamic education in Singapore by tracing its past achievements, the present dilemmas and its future prospects. The writer believes that madrasah education will continue to be relevant that provided appropriate changes are made to keep it in tandem with the changing realities.